Identification of the Determinants of the Effectiveness of On-Road Chicanes in the Village Transition Zones Subject to a 50 km/h Speed Limit - Sołowczuk, Alicja Barbara; Kacprzak, Dominik (Energies (Basel), 2021)
In recent years, in which a considerable increase in the road traffic volumes has been witnessed, traffic calming has become one the key issues in the area of road engineering. This concerns, in particular, trunk roads passing through small villages with a population of up to 500 and the road section length within the village limits of ca. 1400–1700 m. A successful traffic calming scheme must involve primarily effective reduction in inbound traffic speed. A review of the data from various countries revealed that chicanes installed in the transition zones may have a determining effect on the success of the traffic calming project. The effectiveness of such chicanes depends mainly on the type of chicane, its location on the carriageway, its shape and the size of the lateral deflection imposed by the chicane on the inbound lane. The purpose of this study was to identify the speed reduction determinants in traffic calming schemes in village transition zones, based on a central island horizontally deflecting one lane of a two-lane two-way road with 50 km/h speed restriction. As part of the study, vehicle speeds were measured just before and after the chicanes under analysis. Furthermore, the inbound lane traffic volumes were measured in field and a number of factors were identified, including the applied traffic management scheme, road parameters, view of the road ahead and of the village skyline, isolated buildings, road infrastructure and adjacent roadside developments. The obtained data were analysed with a method employing tautologies of the selected 32 factors affecting the drivers’ perception. A single aggregate parameter was proposed for assessing the coincidence of the influence of selected factors on speed reduction. The analysis of the existing schemes and the results of statistical analyses carried out in this study confirmed the authors’ hypothesis that the combined selected factors produce a desirable effect and that they should be additionally enhanced by the application of solar powered devices.